2013
DOI: 10.1021/am403039u
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Quenching of a Chromophore Luminescence by Color Transition of a Polydiacetylene

Abstract: A new reactive diacetylene molecule has been synthesized, incorporating a strongly luminescent chromophore, tetrazine (Tz). It readily polymerizes into the blue polydiacetylene (PDA) form, quenching the Tz luminescence already at concentrations ≤1 %. The blue to red PDA transition is thermally induced in the solid state and the original strong Tz emission is restored. This might lead to a new type of detection for sensors using the PDA color transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The blue color polymer was subjected to Raman analysis, in which the vibration at 2258 cm −1 completely disappeared and two new vibrations appeared, one broad vibration, distinguished as 1463 and 1508 cm −1 , and another at 2088 cm −1 shown in Figure b. The peaks at ≈ 2086 ± ≈ 8 and ≈ 1456 ± ≈ 8 cm −1 are characteristic peaks of CC and CC, respectively, of PDA polymers in its blue phase . Similar observation was also seen for the polymer of 2 (Figure c,d).…”
Section: Resultssupporting
confidence: 68%
“…The blue color polymer was subjected to Raman analysis, in which the vibration at 2258 cm −1 completely disappeared and two new vibrations appeared, one broad vibration, distinguished as 1463 and 1508 cm −1 , and another at 2088 cm −1 shown in Figure b. The peaks at ≈ 2086 ± ≈ 8 and ≈ 1456 ± ≈ 8 cm −1 are characteristic peaks of CC and CC, respectively, of PDA polymers in its blue phase . Similar observation was also seen for the polymer of 2 (Figure c,d).…”
Section: Resultssupporting
confidence: 68%
“…15 A wide variety of stimuli such as temperature, chemo-or bio-specific binding, pH, ions, [16][17][18] and mechanical forces 4,13,19,20 have been shown to trigger the transition. Furthermore, we have shown that it is possible to obtain a thermofluorochromic system with an excellent off to on contrast 21 , despite a low polymerisation rate, by covalently attaching the diacetylene to an appropriate fluorophore, namely tetrazine (Tz) 22 . Before polymerisation, tetrazine is fluorescent in solid state.…”
mentioning
confidence: 99%
“…Polymerization abolished this Raman vibration and two new vibrations, one at 1504 and another at 2110 cm −1 , appeared. These vibrations are characteristic of alternate double and triple bonds, respectively, of ene–yne backbone of the polymer …”
Section: Resultsmentioning
confidence: 99%
“…These vibrations are characteristic of alternate double and triple bonds, respectively, of ene-yne backbone of the polymer. [23][24][25] Thermochromism in the solid state was verified on dried film drop-cast on glass and quartz substrates, by heating the sample under argon atmosphere. Upon heating to 125 °C, the blue color film changed to purple, then to red and finally to orange color.…”
Section: Thermochromism In the Solid Statementioning
confidence: 99%